Teacher Training and Continuing Professional Development: The Singapore Model - Chew, Lee Chin (Sebelas Maret University, 2016)
This paper presents Singaporeâs initial teacher training and continuing professional development as a possible model of teacher education and preparation. Since the mid-1990s, several educational reforms and initiatives have been introduced into Singapore education with the goal of equipping her young citizens with knowledge and skills for a globalised economy and workforce, and for the challenges of the 21st century. Teachers are the frontline of any educational endeavour, which means that teacher quality is paramount to its implementation. Thus, the Ministry of Education invested heavily in building the teacher workforce and enhancing its quality in pursuit of the desired educational outcomes. Increased and sustained teacher recruitment enlarged the teacher workforce. Stringent criteria were used to select suitably qualified applicants who went through intensive pre-service teacher training at Singaporeâs sole teacher training institute, the National Institute of Education. Several policies were put in place to enable in-service teachers to continually develop and upgrade themselves professionally. For instance, every teacher was entitled to 100 hours per year of professional development. A multi-prong approach was deployed to encourage teachersâ participation in professional training and development. These included workshops or short courses for deepening knowledge of subjects taught and for enhancing pedagogical skills, and conference or seminar attendance for sharing teaching practices and broadening experiences. Teachers were also initiated into âlife-long learningâ with various sponsorship schemes to pursue masters or doctoral level studies. On the belief that an educational system is as good as the quality of its teachers, this paper concludes with a discussion of Singapore educationâs continuing journey towards innovations in teacher development.